Plasma Sodium Levels and Dietary Sodium Intake in Manual Workers in the Middle East - Holmes, Nicola; Miller, Veronica; Schneider, J.; Hasan, O.; Bates, Graham (Oxford University Press, 2011)
Objectives: To investigate the hypothesis that workers who consume a predominately rice-based, low-sodium diet and perform long periods of manual work in the heat are at risk of chronic hyponatraemia due to inadequate replacement of sweat sodium losses. Methods: Plasma sodium levels were assessed at the end of both the summer and winter periods in 44 male dockyard workers in the Middle East. The dietary intake of these workers was recorded and analysed by an Accredited Practicing Dietitian to determine average daily sodium intake. Results: 55% of workers were found to be clinically hyponatraemic during the summer period compared with only 8% during the winter period. Assessment of the daily diet of workers in the labour camp revealed it to be predominantly starch based with low total sodium content. The majority of the fluids provided to workers are also low in sodium content. Conclusions: Manual labourers working in the heat and eating a low-sodium starch-based diet are at risk of chronic hyponatraemia. Increasing the sodium content of fluid and food provided to workers is warranted and may reduce the incidence of work-related illness and accidents in this population. The results of this study identify a need for sodium replacement guidelines specific for prolonged work in the heat to be developed.